2010
DOI: 10.1590/s0103-84782010000900011
|View full text |Cite
|
Sign up to set email alerts
|

Diodos emissores de luz e concentrações de BAP na multiplicação in vitro de morangueiro

Abstract: RESUMO Realizou-se um estudo para avaliar o efeito de fontes de luz na micropropagação de morangueiro, com níveis crescentes de BAP no meio de cultivo. Para tanto, inocularamse gemas de brotações da cultivar 'Sabrosa' em meio MS com BAP (0; 0,3; 0,6; 0,9; e 1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 14 publications
(11 reference statements)
1
19
0
11
Order By: Relevance
“…Average plantlet length showed intermediate values under Growlux fluorescent lamps and green LEDs, and the least values under white fluorescent lamps and blue LEDs (Table 1). Kim et al (2004) and Rocha et al (2010) had already observed longer plantlets of chrysanthemum and strawberry when grown under red LEDs than under other sources of light. With other potato cultivars, Wilson et al (1993) obtained longer plantlets under red LEDs, compared to plantlets grown under white fluorescent lamps or even under blue LEDs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Average plantlet length showed intermediate values under Growlux fluorescent lamps and green LEDs, and the least values under white fluorescent lamps and blue LEDs (Table 1). Kim et al (2004) and Rocha et al (2010) had already observed longer plantlets of chrysanthemum and strawberry when grown under red LEDs than under other sources of light. With other potato cultivars, Wilson et al (1993) obtained longer plantlets under red LEDs, compared to plantlets grown under white fluorescent lamps or even under blue LEDs.…”
Section: Resultsmentioning
confidence: 99%
“…LEDs provide radiant energy for better potato explant and plantlet development in laboratory rooms, and also, they show the advantage of longer useful life that may reach 100,000 hours, meanwhile fluorescent lamps present an average useful life of 8,000 hours, and incandescent lamps of 1,000 hours (ROCHA et al, 2010). According to these authors, another advantage is the energy saving, since LEDs present high energetic efficiency (50%) compared to fluorescent lamps (20%) and incandescent lamps (5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater chlorophyll a and b content was found in plants grown in the simplified medium for light sources L4 and L7. Rocha et al (2010) and Nhut et al (2003) observed greater chlorophyll content in strawberry shoots under red and red combined with blue LEDs, respectively. Light source L4 shows a tendency to red, corroborating with these authors' findings.…”
Section: Resultsmentioning
confidence: 93%
“…Although currently fluorescent lights are the most used (POUDEL et al, 2008), studies have been carried out to investigate the quality of the light emitted by LEDs (Light Emitting Diode) in promoting growth and morphogenesis in seedlings propagated in vitro (HEO et al, 2006;MENGXI et al, 2011;ROCHA et al, 2010). In addition, they found signs that the quality of light may affect the plants acclimatization process (NHUT et al, 2005).…”
Section: Introductionmentioning
confidence: 99%